Monitoring Soil Quality in Cassava Cultivation Through Organic Matter Management - Akhmad Farizal Akhsoni (Contributions of Central Research Institute for Agriculture, 2021)
This study aims to study the effect of applying organic matter to improving soil quality and to study the effect of improving soil quality on cassava production. Cassava plants (Manihot esculenta Crantz) are future crops, in which case the commodities cultivated in agriculture in today's society this is very monotonous, without any changes, for example by planting rice, corn or other grain crops, which is continuously carried out in farming communities. The various characteristics of cassava plants strengthen the notion that cassava is a plant that can accelerate land degradation. This assumption seems to be justified by the fact that most cassava plantations are marginal lands. Cassava centers are generally located in areas of marginal land (dry land) which have suboptimal physical characteristics including: sensitivity to erosion and low fertility. Facing these conditions, increasing land productivity is the main requirement for achieving the target of increasing the optimization of sustainable cassava production. Achieving sustainable land productivity can be done through a land maintenance system approach. The land maintenance system is a continuous and comprehensive improvement and monitoring concept compared to land conservation. One of them is by managing organic matter and monitoring soil quality. This study used 30 plots with 10 treatments and 3 replications where each plot was 8 m x 4 m in size.